Roti-Beti Bonds: Exploring the Cultural and Literary Kinship Between Nepal and India - Tharu, Raj Kumar (Academia Research Journal, 2025)
This paper examines the cultural and literary ties between Nepal and India, focusing on their interdependence's historical and contemporary facets. The study which relies upon a verity of secondary sources, examines how cultural and literary contacts have led to the formation of a familial relationship between the two countries. The qualitative study illustrates the rich and complicated nature of this relationship, which has been influenced by common linguistic, religious, cultural, and economic traditions as well as political and economic forces. Through an examination of major texts, this article explores how literature has worked as a channel for the flow of ideas, beliefs, and experiences between the two countries. Furthermore, it examines the problems and opportunities posed by this relationship in the context of the region's shifting social, economic, and political realities by emphasizing the significance of cultural and literary interchange in fostering mutual understanding and cooperation between Nepal and India, as well as the need for continuing communication and collaboration in the years to come. The paper concludes that the two ever-closest South Asian countries- Nepal and India- and their peoples, despite having geographically and politically distinct identities, have been part of the same family for centuries due to the deep similarities and connections among cultural, literary, linguistic, and religious aspects, as well as other social factors.